PEMUTAKHIRAN KURIKULUM DI PERGURUAN TINGGI AGAMA ISLAM - A. Rusdiana (JURNAL ISTEK, 2012)
Updating curriculum is a strategic and dynamic activity in order to increase the quality of education in all educational institutions, especially at university. The study is focused on updating curriculum at university as it is as a strategic educational institution and determines the preparation for qualified people in society. Besides, there is a right of owning the autonomy in educational organization. Many ways can be done by colleges when they want to update their curriculums, such as by using system approach. If this way is used, the colleges are able to conduct updating curriculum activity in planned and accountable way. It is in line with the spirit of the organization of higher education nowadays, to have clear and transparent planning, and become accountable. The activity of Updating curriculum is entirely done and divided according to the needs of the colleges. However, the activity of updating curriculum is obviously focused on considering of the substance competence formula and syllabus form, implementation, and evaluation system. By taking into account target, the curriculum can meet its function as the main of educational activity at university.